Analisis Kemampuan Mahasiswa Calon Guru Menyusun Instrumen Penilaian Kognitif dan Afektif - Mariyani Mariyani; Umi Chotimah; Ammela Anggun Mauilida; Inayah Khairunisa (Ideas Publishing, 2023)
The ability to develop cognitive-affective assessment instruments is an important pedagogical ability so that educational goals can be implemented on target. The aim of this study was to analyze the ability of student teacher candidates to develop cognitive and affective assessment instruments. This study uses descriptive quantitative data collection techniques in the form of questionnaires, observation and documentation. The results showed that there were still several procedures for preparing instruments that were not quite right, difficulties in determining the type of affective assessment that fit the learning objectives so that it was necessary to carry out training in preparing cognitive and affective assessment instruments both in terms of knowledge and practice, especially in terms of the quality of the preparation of instruments at the HOTS level and grammar skills.